ANALISIS FAKTOR PENGGUNAAN LAYANAN GO-PAY OLEH GENERASI Z DALAM MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Wardhani, Ayu Riya; Setiawati, Erma (ITB AAS Indonesia Surakarta, 2025)
Advances in payment technology have shifted the role of the cash system to a non-cash system. Generation Z plays an important role in the adoption of this technology. One of the service innovations of PT. GoTo Gojek Tokopedia Tbk (GOTO) is a GoPay application, which was launched nationally on July 26 2023. This application offers various digital payment services via server-based e-money and e-wallet for customers. GoPay was previously a feature of the Gojek platform, but has now developed into a separate application with exclusive features. This research aims to analyze the factors that influence GoPay usage behavior among Generation Z based on the Unified Theory of Acceptance and Use of Technology (UTAUT). This research used a quantitative method involving 155 respondents collected via an online questionnaire. Data was analyzed using smartPLS. The research results show that work expectations and social influence have a positive influence on GoPay behavioral intentions in Generation Z. On the other hand, business expectations and facilitating conditions have no influence. It is hoped that these findings can support strategies to increase GoPay adoption among Generation Z.